2018
DOI: 10.3329/cmoshmcj.v16i2.37293
|View full text |Cite
|
Sign up to set email alerts
|

Management of Distal Femoral Fracture with Distal Femoral Nail

Abstract: Background: For a long time distal femur fracture were considered difficult to heal and often led to a degree of disability. The incidence of malunion, nonunion and infection are relatively high in many reported series. The management goal of distal femur fractures are correction of axial alignment, length, and rotation, restoration of motion and rapid union so as to return the patient to normal function. We present here result of retrograde nailing of extra-articular (AO 33A1 to A3) fractures of the distal fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
3
2
0
Order By: Relevance
“…12 No non-union occurred in present series. Similar finding was found in the series of Gellman et al, Jahangir et al, and Loya et al 5,8,11 But Anaberu et al, Handolin et al found non-union of 2.65% and 4.7% cases respectively in their series. 12,13 A study by Dileep et al showed 3 (14.3%) cases of delayed union.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…12 No non-union occurred in present series. Similar finding was found in the series of Gellman et al, Jahangir et al, and Loya et al 5,8,11 But Anaberu et al, Handolin et al found non-union of 2.65% and 4.7% cases respectively in their series. 12,13 A study by Dileep et al showed 3 (14.3%) cases of delayed union.…”
Section: Discussionsupporting
confidence: 88%
“…This was comparable with the study conducted by Loya et al, Jahangir et al where mean duration of fracture union was 16 weeks and 15.81 weeks respectively. 5,8 100 percent of the fractures were healed in our study. Similar findings were seen in series of Gellman et al, Jahangir et al, Loya et al and Dileep et al 5,8,9,11 But in the series of Handolin et al 95% of the fractures were healed in regular healing time (less than 24 weeks).…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations